Diagnostic Value of Encode TB IgG and IgM Rapid Test to Support Pulmonary Tuberculosis Diagnosis - Notrisia Rachmayanti; Aryati Aryati; Tutik Kusmiati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Diagnosis of tuberculosis can be established through the detection of antigens by Acid Fast Bacilli (AFB), microscopy, culture, and Polymerase Chain Reaction (PCR). The World Health Organization (WHO) 2012 issued a recommendation not to use antibody detection in the diagnosis of tuberculosis. However, there is high demand from clinicians to detect anti-tuberculosis antibody in patients who are challenging to do a bacteriological examination. The purpose of this research was to determine the diagnostic value of anti-M.tuberculosis IgG and IgM Encode TB to support lung tuberculosis diagnosis.This study was a cross-sectional by using consecutively sampling, which was performed in the Dr. Soetomo Hospital, Surabaya, Indonesia, from November 2017 until May 2018. A total of 52 patients were included and evaluated for clinical or bacteriological examination using AFB microscopy or PCR (Gene Xpert) as the gold standard and tested the anti-M.tuberculosis IgG and IgM with immunochromatography. Encode Tuberculosis (TB) IgG was positive in 12 patients from the tuberculosis group and one false-positive in the non-tuberculosis group. The diagnostic sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of Encode TB IgG dan IgM were 35%, 94%, 92%, 43% and 55.7%, respectively. The specificity was high that the positive result was considered as TB; the sensitivity was low that the negative results were not excluded from TB. Encode TB IgG/IgM rapid test was not recommended to use as a single diagnostic test and must be combined with other diagnostic tests to increase the sensitivity.